2004
DOI: 10.1583/04-1269mr.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probucol Versus Aspirin and Versus Brachytherapy on Restenosis After Femoropopliteal Angioplasty:The PAB Randomized Multicenter Trial

Abstract: Endovascular brachytherapy significantly reduces restenosis, improves symptoms, and reduces reinterventions after PTA of femoropopliteal arteries. Probucol reduces restenosis but has no additive effect when combined with brachytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Gallino et al 82 reported results of a 2 ϫ 2 factorial randomized trial of 335 patients assigned to PTA, PTA plus BT (14 Gy), PTA plus probucol, or PTA plus probucol and BT. No late thrombotic reocclusion occurred after PTA and subsequent BT.…”
Section: Brachytherapymentioning
confidence: 99%
“…Gallino et al 82 reported results of a 2 ϫ 2 factorial randomized trial of 335 patients assigned to PTA, PTA plus BT (14 Gy), PTA plus probucol, or PTA plus probucol and BT. No late thrombotic reocclusion occurred after PTA and subsequent BT.…”
Section: Brachytherapymentioning
confidence: 99%
“…Krueger et al [29] reported a significant reduction of restenosis following PTA of de novo lesions in the femoropopliteal area in the brachytherapy group compared to the control group. Gallino et al [15] also stressed the beneficial effect of endovascular brachytherapy in fighting restenosis (17% restenosis rates in the brachytherapy group vs. 35% in the patients without brachytherapy; p < 0.001). However, they pointed out that they observed late thrombotic occlusions exclusively in six of 133 patients of the brachytherapy group versus none in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 In the femoral segment, acute stent thrombosis within the first 6 months occurred in 21% to 27% of the patients receiving nitinol stents and EVBT. 17,26 In both reports, late acute stent thrombosis was synchronous with reduction of the double antiplatelet regimen. For this reason, many authors recommend double antiplatelet therapy for at least 1 year to prevent late thrombotic occlusions after EVBT.…”
Section: ¤ ¤mentioning
confidence: 97%